THE DEVELOPMENT OF ASSESSMENT INSTRUMENT OF REASONING ABILITY ON HOTS FOR PHYSICS LEARNING - Yetti Supriyati (JISAE (Journal of Indonesian Student Assessment and Evaluation))
The purpose of this study is to develop an assessment instrument of reasoning ability on HOTS-based science learning assessment model on the Primary School Education Program’s students. The research method used is a research and development method. This method developed the evaluation model of HOTS-based science learning assessment that has the characteristics to measure the ability of deductive hypothesis between variables, to predict phenomenom represent it with logical thinking. Moreover to analyze theoretical statement by using if-then provison. HOTS-based science learning assessment model is validated by physics education experts and science education practitioners. After that, the assessment tools were tested by students in the Primary School Education Program. The result showed that the assessment model has 7 items characteristic deductive hypothesis that valid and reliable.